Mark Twain's Audience : a critical analysis of reader responses to the writings of Mark Twain - McParland, Robert (Lexington Books, 2014)
The unique contribution of this book is the focus upon the testimony of Twain's audience as a unique "reading community"--How his fiction intersected with their real lives, how he impacted American publishing, literacy, and educational reform, and how Americans loved the theatricality and humor that Twain brought to their lives